Nisekoi : False love. Vol. 3, What's in a name? - Komi, Naoshi, 1986- (Shonen Jump manga., 2014)
In order to keep the peace between their feuding gang families, Japanese high school students Raku Ichijou and Chioge Kirisaki agree to pretend they are in a romantic relationship. Everyone at school is fooled, even Raku's crush, Onodera. Raku wants her to know the truth, but he can't seem to find a way to tell her.